Psychological distress problems among ischemic heart disease (ihd) patients in Medical Wards, Hospital Universiti Sains Malaysia - Halim, Norhasyini Abdul (Universiti Sains Malaysia, 2015)
The present study was attempted to study the anxiety and depression on ischeamic heart disease (IHD). The purposive sampling method was adopted to select the sample. The sample was consisted of 61 subjects with ischeamic heart disease (IHD) for both males and females was selected from medical wards Hospital Universiti Sains Malaysia (Hospital USM). The instrument used Cardiac Anxiety Questionnaire (CAQ). The goal for this study is to determine the level of psychological distress among IHD patients in medical wards Hospital USM. Second goals is to determine the difference between gender and psychological distress among IHD patients and also to determine the association between selected demographic data (age, marital status, and educational level) and psychological distress among IHD patients in medical wards Hospital USM. Data were collected from January to March 2015 and analyzed using SPSS version 20.0 for frequency, percentage, mean, standard deviation and p-value. The overall score of psychological distress patients with IHD was at the low level of stress (mean = 35.10). Majority of the respondent have low level of psychological distress (54.10 %) and remaining is high score of psychological distress (45.90%).The study found that there was significant difference between gender and psychological distress among IHD patients. It was also found that there was significant association between selected demographic data (age and level of education) and psychological distress while for marital status there was no significant association with the psychological distress. Thus, nurses should identify the psychological distress in order to improve the management of psychological distress as well as quality of nursing care in order to prevent further complications to the IHD patients.